Close Association between Awareness of Teeth-Alignment Disorder and Systemic Disorders in Late Adolescence - Abe, Masanobu; Mitani, Akihisa; Yao, Atsushi; Zhang, Chun-Dong; Hoshi, Kazuto; Yanagimoto, Shintaro (Healthcare (Basel), 2021)
Background: Oral diseases are associated with various systemic disorders. Our previous research revealed new insights into the close relationship between occlusal disorder (functional disorder) and systemic disorders (allergic rhinitis, asthma, and arrhythmia) in late adolescence. Here, we investigated whether there was an association between the awareness of teeth-alignment disorder (morphological disorder) and common systemic disorders. Subjects and Methods: We retrospectively reviewed the data of the mandatory medical questionnaire that is required for the freshman medical checkup in Japan. We collected the data of all students who completed the questionnaire between April 2017 and April 2019. The data were analyzed using the χ2 test, and a multivariate analysis was performed with a binomial logistic regression model. Results: The subjects were 8903 students aged 17–19 who had no awareness of occlusal disorder. The rate of awareness of teeth-alignment disorder was 20.43% (1819 of 8903 eligible subjects), and the aware students had significantly greater rates of gum bleeding (p < 0.001), pollinosis (n = 0.007), and atopic dermatitis (n = 0.042). The multivariate analysis revealed significant rates of gum bleeding (odds ratio (OR) 1.540, 95% confidence interval (CI): 1.386–1.711, p < 0.001), pollinosis (OR 1.197, 95% CI: 1.040–1.378, p = 0.012), and female gender (OR 1.141, 95% CI: 1.002–1.299, p = 0.046) among the students with awareness of teeth-alignment disorder. Conclusion: We identified close associations between the awareness of teeth-alignment disorder and both gum bleeding and pollinosis in a late-adolescent population. The systemic disorders that are targeted by teeth-alignment disorder were found to be different from those targeted by occlusal disorder.